Effects of bovine seminal plasma on frozen semen quality of swamp buffaloes (Bubalus bubalis - Muhammad Rizal Amin; Mozes R Toelihere; tuty L Yusuf; Polmer Situmorang (Jurnal Ilmu Ternak dan Veteriner, 1999)
Semen of two healthy swamp buffalo bulls were collected twice a week using artificial vagina. After initial evaluation, semen was divided into two parts, 1/3 for control (PK) and 2/3 for treatment (PS) and centrifugated at 3,000 rpm for 20 minutes. Seminal plasma of the second part was removed and changed with bovine seminal plasma for 0 minute (PS0) and 5 minutes (PS5) before semen was diluted with lactose extender containing 7% glycerol. Mean percentage of motility after thawing for PS5 (55.71%) was significantly higher (P<0.01) than PK (41.43%), but not significantly different with PS0 (52.43%). PS0 was significantly higher than PK. Mean percentage of live sperm and intact plasma membrane for PS5 (63.43% and 64.71%) were significantly higher (P<0.01) than PK (55.71% and 53.57%), but not significantly different with PS0 (61.14% and 59.28%). There was no significantly difference between PS0 and PK for mean percentage of live sperm and intact plasma membrane parameters. Mean percentage of intact acrosomal for PS5 (53.57%) was significantly higher (P<0.01) than PS0 (48.14%) and PK (43.14%). PS0 was significantly higher (P<0.01) than PK. Under conditions of these experiment it may be concluded that replacement of buffalo seminal plasma with bovine seminal plasma and diluted with lactose extender could improve of frozen semen quality of swamp buffaloes.   Key words : Cattle seminal plasma, frozen semen, swamp buffalo